THE RELATIONSHIP BETWEEN MINIMUM WAGE POLICY, HUMAN CAPITAL INVESTMENT, AND ECONOMIC GROWTH - Gunawan Widjaja (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2024)
The relationship between minimum wage policy, human capital investment, and economic growth refers to the complex interaction between three key elements in economic development. Minimum wage policy is a government regulation that sets the lowest limit of wages to be paid to workers. Human capital investment involves efforts to improve the quality and capacity of the workforce through education, training and skills development. Meanwhile, economic growth refers to the increase in the production capacity of goods and services in an economy over time. This relationship illustrates how the right wage policy and investment in human capital can work together to boost productivity, innovation, and ultimately sustainable economic growth. The research method uses a literature review. The results show that an appropriate minimum wage policy can improve workers' living standards and encourage consumption, but needs to be implemented carefully to avoid negative impacts on employment. Investments in human capital through education and training are proven to increase productivity and innovation, which in turn boost economic growth. The study concludes that a balanced and integrated approach in managing minimum wage policy and human capital investment is essential to achieve sustainable and inclusive economic growth.